The nature communication and relationship between migrant parents and left-behind children. - Cabigunda, Gael J.
This study is qualitative in nature which sought to describe the nature of communication between migrant parents and left-behind children and to describe how their communication influenced their relationship and the balance of the family unit despite the physical separation and the distance. The family system?s theory was used as framework in this study, to better explain the nature of communication and the relationship between migrant parents and left-behind children among transnational families. Twenty-two (22) left-behind children were conveniently sampled to participate in focus group discussions conducted by researchers. Experiences of left-behind children on migration were captured through the use of an interview guide which included questions pertaining to: (1) the methods used in communication, (2) the problems encountered in communication, (3) the content of the communication and (4) the parent-child relationship. Data was then analyzed using thematic analysis. Results showed that the nature of communication and relationship between migrant parents and left-behind children are dependent on: the characteristics of the parent and the child, the methods used in communication, the existing relationship before migration occurred, and the guardian?s role in the triangle relationship. In conclusion, the frequency of communication served as an affirmation of the existing relationship between parent and child. Furthermore, when the parent and child have an open relationship, they enjoy a better quality of communication. Communication was also used by parent and child to fulfil their roles and affirm their membership in the family despite physical separation and the distance.